Strategi Manajemen Konflik Interpersonal dalam Transformasi Digital Layanan Publik: Studi Kasus Dinas Kependudukan dan Pencatatan Sipil (Dispendukcapil) Kota Surabaya - Ika Bima; Putri ishmah Widayati; Farida Fauzia Ihsani; Nuh Krama Hadianto (Jurnal Ilmu Administrasi Negara, 2026)
Digital transformation in public services has become a strategic effort by local governments to create a more efficient, transparent, and responsive bureaucracy. Surabaya City, as one of the pioneers of Smart City implementation in Indonesia, introduced the Klampid New Generation application to facilitate population administration services for the community. However, the digitalization process has triggered interpersonal conflicts within the Department of Population and Civil Registration (Dispendukcapil), particularly between senior employees who are accustomed to manual systems and younger employees who are more adaptive to technology. This study aims to analyze the forms of interpersonal conflict, the factors causing the conflict, and conflict management strategies in supporting the digital transformation of public services. The study employed a qualitative approach using a literature study method through descriptive analysis of various relevant scientific sources. The results show that relationship conflict and process conflict are the most dominant forms of conflict. These conflicts are influenced by limited digital literacy, lack of continuous training, human error, and a traditional bureaucratic culture that has not fully adapted to change. Conflict management strategies such as collaboration, accommodation, compromise, and open communication have proven effective in reducing tension among employees and improving teamwork. This study concludes that the success of digital transformation depends not only on technological readiness but also on the organization’s ability to build an adaptive work culture, effective communication, and the strengthening of human resource capacity. Keywords: Interpersonal Conflict, Conflict Management, Digital Transformation, Public Service, Public Organization.